2023
DOI: 10.3390/rs15020408
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Evaluation and Branch Detection Method of 3D Modeling Using Backpack 3D Lidar SLAM and UAV-SfM for Peach Trees during the Pruning Period in Winter

Abstract: In the winter pruning operation of deciduous fruit trees, the number of pruning branches and the structure of the main branches greatly influence the future growth of the fruit trees and the final harvest volume. Terrestrial laser scanning (TLS) is considered a feasible method for the 3D modeling of trees, but it is not suitable for large-scale inspection. The simultaneous localization and mapping (SLAM) technique makes it possible to move the lidar on the ground and model quickly, but it is not useful enough … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Teng et al ( 2023) compared both LiDAR-based SLAM and SFM. In their research, they found SLAM to be faster and more accurate than SFM [98]. For better visualization, an illustration of 3D object detection technique stages is presented in Figure 2 in a very simplified manner.…”
Section: Other 3d Object Detection Methodsmentioning
confidence: 99%
“…Teng et al ( 2023) compared both LiDAR-based SLAM and SFM. In their research, they found SLAM to be faster and more accurate than SFM [98]. For better visualization, an illustration of 3D object detection technique stages is presented in Figure 2 in a very simplified manner.…”
Section: Other 3d Object Detection Methodsmentioning
confidence: 99%